Hubungan Kematangan Emosi dalam Pengambilan Keputusan Karir Siswa - Vereyra, Salsabilla; Fitria, Linda (Journal of Research and Investigation in Education, 2023)
The purpose of this study was to determine the relationship between emotional maturity in decision making, the level of emotional maturity and decision making. The hypothesis of this research is that there is a positive relationship between emotional maturity and decision making. The subjects of this study were 119 students of SMK Negeri 9 Padang. The sampling technique used in this research is simple random sampling. The method uses a quantitative approach with measuring tools of emotional maturity scale and decision making scale. The data analysis technique used in this research is non-test using a psychological scale. Meanwhile, the tools used to collect data are emotional maturity scale and career decision-making scale which were developed based on theoretical studies. The scale contains several statements that aim to determine the psychological attributes of the respondents, namely the attributes of emotional maturity and career decision-making attributes. The scale used in this study is the Likert scale model. Based on the results of data analysis obtained a correlation coefficient of 0.878 with a significance level of 0.000 compared with a probability of 0.05 then 0.000 <0.05. The analysis was carried out using SPSS 20